THE ROLE OF MARKETING IN CORPORATE COMPETITIVENESS: MARKETING PRACTICE ANALYSIS OF HUNGARIAN COMPANIES - Zsófia KENESEI; Tamás GYULAVÁRI; László SEER (Management & Marketing)
The objective of this article is to analyse the marketing practice of Hungarian companies. On the one hand, the role of marketing function in the company has been revealed, and on the other hand the relationship between marketing efforts and market performance has been investigated. In frame of the Hungarian Competitiveness Studies, 300 marketing executives were surveyed to rate the marketing practice of their companies, concentrating on branding, pricing policy, applied marketing channels and promotional activities. The results confirm that sophisticated marketing practice leads to higher business performance.